Risky Behaviors among HIV-Positive Female Sex Workers in Northern Karnataka, India. (9th January 2013) - Jadhav, Apoorva; Bhattacharjee, Parinita; Raghavendra, T.; Blanchard, James; Moses, Stephen; Isac, Shajy; Halli, Shiva S.
Abstract : Purpose . Little is known about the risky sexual behaviors of HIV-positive female sex workers (FSWs) in the developing world, which is critical for programmatic purposes. This study aims to shed light on their condom use with regular clients as well as husband/cohabiting partner, a first in India. Methods . Multivariate logistic regression analyses for consistent condom use with regular clients and husband/cohabiting partner are conducted for the sample of 606 HIV-positive FSWs. Results . Older FSWs are 90% less likely and nonmobile FSWs are 70% less likely to consistently use condoms. FSWs on ART are 3.84 times more likely to use condoms. Additionally, FSWs who changed their occupation after HIV diagnosis are 70% less likely to use condoms. FSWs who are currently cohabiting are more likely to consistently use condoms with repeat clients and are 3.22 times more likely to do so if they have felt stigma associated with being HIV-positive. FSWs who have multiple repeat clients, and who do not know the sexual behavior of these clients, are more likely to use condoms consistently. Conclusion . This study would help inform programs to target the following particularly vulnerable HIV-positive FSWs: those who are older, those who changed their occupation post-HIV diagnosis, and those who are nonmobile.